Evaluation of Corporate Identity Design on Company Image: A Case Study of CV. Nova Tritama Kapas Bojonegoro: Evaluasi Desain Identitas Korporat Terhadap Citra PerusahaanStudi Kasus: CV. Nova Tritama Kapas Bojonegoro - Arfa, Daghastaniy Fairuzza; Sharf, Oely Maqwa; Hakim, M. Luqmanul; N.J, Branita Shandyni; Khairunnisa, Irma (Academia Open, 2024)
The development of digitalisation has had a significant impact on industry dynamics, particularly in driving the transformation of micro, small, and medium enterprises (MSMEs). In this context, corporate identity design serves not only as a visual element but also as a strategic representation for building a strong and memorable company image in the minds of consumers. This study aims to evaluate the influence of corporate identity design on company image at CV. Nova Tritama, an SME in Bojonegoro Regency engaged in food production. A descriptive qualitative approach was used with a case study method, employing observation, in-depth interviews, and documentation of the rebranding process. The results of the study indicate that corporate identity design plays a crucial role in enhancing brand recognition, strengthening perceptions of professionalism, and building positive brand equity. A strong visual identity has proven to facilitate consumers in recognising, remembering, and trusting products, thereby directly contributing to improved competitiveness and market confidence in SMEs.